Pengaruh Persepsi Kemudahan Penggunaan dan Kepercayaan terhadap Loyalitas Pengguna E-wallet DANA dengan Kepuasan Sebagai Variabel Intervening - Raudatussyifa, Amani; Rose Rahmidani (Jurnal Economic Resource, 2025)
The purpose of this study is to analyze the influence of Perceived Ease of Use and Trust on DANA E-wallet User Loyalty, with Satisfaction as an intervening variable. The population in this study were students of Padang State University who had used the DANA e-wallet more than twice, the number of which is unknown. The sample determination in this study was 100 people using a purposive sampling technique. Data were collected through a questionnaire with a Likert scale. The analysis method used was SEM with the SmartPLS 4.0 approach. The results showed that Perceived Ease of Use and Trust have a positive and significant influence on User Satisfaction. Furthermore, Satisfaction was proven to have a positive and significant influence on User Loyalty. Although Perceived Ease of Use and Trust do not show a significant direct influence on Loyalty, the mediating role of Satisfaction is very important in shaping the loyalty of DANA E-wallet users. This finding confirms that user satisfaction is important in driving the formation of loyalty in the context of using digital financial services.